Efektivitas Learning Management System Terhadap Pelayanan Administrasi Pembelajaran di MTs Plus Nurul Falah Jabres - Nurchayati, Anisa Dwi; Gunawan, Yosi Intan Pandini (Jurnal Kridatama Sains dan Teknologi, 2023)
In Indonesia, there are many schools whose administrative system for teacher learning still uses a manual system, especially at MTs Plus Nurul Falah Jabres Kebumen, so an alternative solution for this administration system is the use of a Learning Management System for teacher learning administration services that can be used anytime and anywhere with an online system. The method used for the development of the Learning Management System uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The purpose of this study is to facilitate administrative services and reduce obstacles in the implementation of administration. The results of the analysis of this study resulted in the effectiveness of the LMS based on validation, response, and practicality in the "Good" category and it can be concluded that the validation results obtained a score of 67.19% in the "Good" category, the response of LMS users obtained a score of 86.71% in the "Very Good" category. and the practicality of the LMS obtained a score of 86.40% in the "Very Good" category so the LMS in teacher learning administration services can be said to be effective.. Keywords: Administration, Learning Management System, Management, ADDIE Model